Acute aflatoxin B1-induced gastro-duodenal and hepatic oxidative damage is preceded by time-dependent hyperlactatemia in rats (2020)
Elevated serum lactate concentration has been used to predict the risk of fatality in various disease states in acutely ill patients or poisoning with different chemicals. However, its utility in predicting disease progression during acute aflatoxicosis has not been investigated. This study was designed to evaluate changes in blood lactate levels following acute exposure to aflatoxin B1 (AFB1) and to determine whether changes in blood lactate levels bear any relationship with biochemical and/or morphological lesions in the stomach, duodenum, and liver. Twenty-one male Wistar rats were randomly divided into three groups (n = 7 rats /group) including Group A (control) receiving vehicle alone and Groups B and C treated with single oral doses of AFB1 at 2.5 and 5 mg/kg, respectively. AFB1 produced significant (p < 0.05) time- and dose-dependent increase in blood lactate concentration as early as 1 h following its administration, with further increases observed at 3 h and 6 h. The hyperlactatemia accompanied tissue oxidative changes including increased H2O2 and MDA, as well as depletion in glutathione, glutathione peroxidase, superoxide dismutase, and total thiols in gastro-duodenal and hepatic tissues. The oxidative changes were reflected in morphological alterations observed at histopathology with more severe lesions observed with the higher dose of AFB1. Serum levels of pro inflammatory cytokines (TNF-α and IL-1β) were, however, differently modified by AFB1 administration. Taken together, the results from this study gives indication that hyperlactatemia may find utility in predicting the severity of tissue damage induced by acute AFB1 exposure.